Exposure to Intimate Partner Violence and Children's Dynamic Skill Accumulation: Evidence from a UK Longitudinal Study - Dan Anderberg; Gloria Moroni (Tinbergen Institute, 2020)
Children are increasingly recognized as secondary victims of intimate partner violence. This paper uses a unique UK longitudinal child development survey to study the relationship between verbal and physical abuse experienced by mothers and children's development up to the age of seven. Estimating production functions for cognitive, social, and socio-emotional skills we find that exposure during pre-school years has a quantitatively important negative effect on socio-emotional skills among toddlers and negatively affects cognitive and social skills after age three. The estimated impact on cognitive development is consistent with measures of cognitive skills based on school-based tests.
Keywords: J12; I14; I24; 330; Domestic violence; child development; skills; ALSPAC